An erosive neritic area of Shantou in coastal NE South China Sea since at least MIS 5 revealed by OSL dating of cores - Zhong, Jiemei; Liu, Bohui; Ou, Yang; Tian, Ruonan; Shan, Jingxiang; Xu, Yantian; Wang, Feng; Abbas, Mahmoud; Zhang, Ke; Lai, Zhongping (Frontiers in Earth Science, 2023)
The neritic region of the Chaoshan Plain is located on the northeastern (NE) boundary of the South China Sea (SCS). Despite the extensive research on the stratigraphic architecture and sedimentary processes within the Chaoshan Plain, the neighboring neritic area remains largely unexplored. In this study, we provide a new set of ages on seventeen quartz optically stimulated luminescence (OSL) dating results from four cores (SY2-2, SY3-1, SY3-2, and HS02) to investigate the regional chronostratigraphy and sedimentology of the area. The samples were collected at depths ranging from 0.6 to 73.5 m and yielded ages ranging from 4.9 ± 0.3 ka to >139 ± 28 ka. Sedimentation thickness from cores SY3-2, SY2-2, and HS02 is less than 4.2 m, 5.5 m, and 6.4 m, respectively, since at least Marine Isotope Stage (MIS) 5, and the Holocene sediments of core SY3-2 are less than 4.2 m thick. The preservation state of the sediments in the area is poor since at least 83.6 ka, indicating an intensified erosion in the neritic region of the northeastern South China Sea (NESCS) since at least MIS 5. This erosion may have been caused by fluvial incision resulting from a sea-level decline during the last glacial period, as well as strong transportation caused by coastal currents.